Bone morphogenetic protein 6 and oxidized low-density lipoprotein synergistically recruit osteogenic differentiation in endothelial cells. (26th September 2015) - Yung, Lai-Ming; Sánchez-Duffhues, Gonzalo; ten Dijke, Peter; Yu, Paul B.
Abstract: Aims: Vascular calcification contributes to mortality and morbidity in atherosclerosis, chronic kidney disease, and diabetes. Vascular calcific lesions contain osteoblast- and chondroblast-like cells, suggesting a process of endochondral or membranous ossification thought to result from the phenotypic plasticity of vascular cells. Bone morphogenetic protein (BMP) signalling potentiates atherosclerotic calcification, whereas BMP inhibition attenuates vascular inflammation and calcification in atherogenic mice. We hypothesized endothelial cells (ECs) may undergo osteogenic differentiation in response to BMP signalling and pro-atherogenic stimuli. Methods and results: Among various BMP ligands tested, BMP6 and BMP9 elicited the most potent signalling in bovine aortic endothelial cells (BAEC), however, only BMP6 induced osteogenic differentiation. BMP6 and oxidized low-density lipoprotein (oxLDL) independently and synergistically induced osteogenic differentiation and mineralization, in a manner consistent with endothelial-to-mesenchymal transition. Treatment of ECs with BMP6 or oxLDL individually induced osteogenic and chondrogenic transcription factors Runx2 and Msx2, whereas treatment with BMP6 and oxLDL synergistically up-regulated Osterix and Osteopontin . Production of H2 O2 was necessary for oxLDL-induced regulation of Runx2, Msx2, and Osterix in BAEC, and H2 O2 was sufficient by itself to up-regulate these genes. Mineralization of ECs in response to BMP6 or oxLDL was abrogated by scavenging reactive oxygen species or inhibiting BMP type I receptor kinases. Similar synergistic effects of BMP and oxLDL upon osteogenic and chondrogenic transcription and phenotypic plasticity in human aortic endothelial cells were observed. Conclusion: These findings provide a potential mechanism for the observed interactions of BMP signalling, oxidative stress, and inflammation in recruiting vascular calcification associated with atherosclerosis.